Super-fast production of drug nanocrystals: Dual asymmetric centrifugation-enabled media milling applied to high throughput formulation screening - Lucia Lopez-Vidal; Maria G. Bordon; Alejandro J. Paredes (Materials & Design)
Drug nanocrystals (NCs) have entirely changed the panorama of drug delivery, enabling enhanced drug absorption and long-acting drug release. The vast majority of marketed NCs-based products are obtained via media milling using of-the-shelf industrial machinery. However, early-stage formulation development is time-consuming and challenging when limited active amounts are available. This study demonstrates the feasibility of producing NCs using dual asymmetric centrifugation (DAC) in a single 1-minute milling cycle. The methodology proved effective for 9 out of 10 evaluated drugs, achieving particle sizes as low as 174 nm. Subsequently, three drugs were selected for an in-depth study of the influence of various parameters on particle size and polydispersity index (PDI). The crystallinity and morphology of the resulting NCs were investigated using thermal analysis and transmission electron microscopy. Potential sample contamination was assessed using nanoparticle tracking analysis, with values < 1 %. A multiple-response optimization study and a microhydrodynamic analysis of the milling established a quantitative relationship between the process variables and particle size. Furthermore, it established that the DAC methodology significantly outperforms conventional laboratory-scale wet media milling in terms of milling efficiency. The findings of this study position DAC as a rapid, cost-effective, and efficient top-down wet media milling method to obtain NCs.